Pembelajaran Bahasa Indonesia dan Sastra (BASASTRA) di SD dan MI - Ummul Khair (Institut Agama Islam Negeri (IAIN) Curup, 2018)
The learning of Bahasa Indonesia in curriculum 13 is the learning based on the text, text is an application of the thing in the human mind which is complete with the situation and context. The application of the learning uses scientific approach with suitable model. The achieving of the KD in the group KI: 1 and 2 are determine by achieving KD in the group, KI: 3 and 4. The meaning of the language based on the function. Its mean the using of the language which is never been separated from the context because the form of the language that used represented the idea, character, values, and ideology of the user